Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.23960/ujet.v10.i1.202108
|View full text |Cite
|
Sign up to set email alerts
|

The use of Picture series on Instagram to improve students’ writing in EFL Writing class

Abstract: Instagram has been used as the medium to upload photos, e.g. picture series. The current research was intended to find out I) whether picture series on Instagram could facilitate students to improve their writing achievement, II) students' perceptions of the use picture series. The design of the research was mixed quantitative and qualitative approaches. The subjects of the research were 31 students of thefirstgradeofSMANegeri2BandarLampung. The data were collected through the writing tests (pre and post-tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…For example, the use of picture series (i.e., Gutierrez, Puello & Galvis, 2015;) story-mapping technique (i.e., Ibnian, 2010;Rahmawati & Cahyono, 2018), clustering technique (i.e., Adriati, 2013), and flowchart (i.e., Selvaraj, et al, 2020). Among all of these techniques, picture series seems promising to improve narrative writing for students who have difficulty finding ideas to write (i.e., Anggita, Mahpul, & Riyantika, 2021Hidayah, Mulyati & Suprojadi, 2019Imastuti, 2013). Pictures may multiply students' motivation to deliver whatever stories they are enthusiastic with; thus, they are willing to do more efforts to finish their writing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the use of picture series (i.e., Gutierrez, Puello & Galvis, 2015;) story-mapping technique (i.e., Ibnian, 2010;Rahmawati & Cahyono, 2018), clustering technique (i.e., Adriati, 2013), and flowchart (i.e., Selvaraj, et al, 2020). Among all of these techniques, picture series seems promising to improve narrative writing for students who have difficulty finding ideas to write (i.e., Anggita, Mahpul, & Riyantika, 2021Hidayah, Mulyati & Suprojadi, 2019Imastuti, 2013). Pictures may multiply students' motivation to deliver whatever stories they are enthusiastic with; thus, they are willing to do more efforts to finish their writing.…”
Section: Introductionmentioning
confidence: 99%
“…In some research, Instagram app has been reported to successfully improve students' writing ability in different genres (i.e., Soviyah & Etikaningsih, 2018;Listiani, 2016). Some researchers have investigated the effectiveness of instagram app to improve EFL writing and they found that it is well accepted among EFL students with satisfying results (i.e., Anggita, Mahpul, & Riyantika, 2021;Soviyah & Etikaningsih, 2018;Listiani, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Nurhayati (2022) asserted that utilizing online proofreading tools was considered helpful in guiding her students to write their texts coherently and maintain writing integrity. Other lecturers made use of social media in mobile apps like Instagram (e.g., Anggita et al, 2021;Saleh & Muhayyang, 2021) and Facebook (Fithriani et al, 2019;Sakkir & Dollah, 2019) to enhance their students' idea development. Web-based-language-learning pages, including Purdue Online Writing Labs, are thought to be valuable sources for using pertinent phrases and clauses in academic contexts, argued Meysarah (2018) and Walisundara (2020).…”
Section: Introductionmentioning
confidence: 99%